Aprendizaje Basado en Retos en el componente de aprendizaje práctico experimental para estudiantes de la Carrera Agronegocios en Universidad Nacional de Loja - Ruiz Vélez, Pablo Fernando (2025)
This research explores Challenges-Based Learning (CBL) within the context of the Agribusiness program at the Distance Learning Unit of the National University of Loja. CBL is an educational methodology designed to prepare students to face real-world challenges in the agri-food sector. The general objective is to analyze practical and experimental competences among Agribusiness students at the National University of Loja through the implementation of Challenge-Based Leaning methodologies, promoting the resolution of real problems in the agricultural sector. The specific objectives are three; 1 To investigate the principles and theories underlying Challenge-Based Learning in order to establish a solid conceptual framework that supports its application in the practical and experimental learning component. 2 To apply assessment tools that allow for the measurement of students’ development in practical and experimental competencies, ensuring the effectiveness of the Challenge-Based Learning methodology. 3 To implement Challenge-Based Learning in the practical and experimental learning component for Agribusiness students at the National University of Loja through a case study. The research used a mixed-methods approach with a correlational design, using descriptive, inductive-deductive and analytical-synthetic methods. A total of 95 undergraduate students and11 instructors participated. The results revealed real-world challenges in the sector, such as crop optimization, product commercialization, and agri-foods supply chain management. Students engaged with situations reflecting current issues in the agri-food industry, including climate change and global market demands. In response to these challenges, the research proposes a set of strategies for the effective implementation of CBL in the practical and experimental learning component.